2020
DOI: 10.1155/2020/5317352
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management and Its Possible Implementation Research in North Ethiopia: A before and after Study

Abstract: Background. Though there is an effective intervention, pain after surgical intervention is undermanaged worldwide. A systematic implementation is required to increase the utilization of available evidence-based intervention to manage the inevitable pain after surgery. The aim of this research project is to develop a scalable model for managing pain after cesarean section by implementing the World Health Organization’s (WHO) pain management guidelines through a combination of implementation research and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The evidence shows that pain is one of the main reasons patients seek medical care [3][4][5][6]. Untreated pain has an impact on patients' clinical and psychological well-being, as well as hastens their risk of mortality and has a slew of other negative repercussions, such as raising treatment expenses, lengthening hospital stays, and lowering their quality of life [2,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence shows that pain is one of the main reasons patients seek medical care [3][4][5][6]. Untreated pain has an impact on patients' clinical and psychological well-being, as well as hastens their risk of mortality and has a slew of other negative repercussions, such as raising treatment expenses, lengthening hospital stays, and lowering their quality of life [2,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Only eight articles mentioned the use of QI methods. Five of these studies used Plan–Do–Study–Act cycles,37 38 43 44 47 one used QI collaboratives,48 and two used audit and feedback as the QI method 49 50. Use of implementation science frameworks was rare with only two studies using frameworks to support intervention implementation and the evaluation of implementation 51 52…”
Section: Resultsmentioning
confidence: 99%
“…We found that almost all the studies focused on either safety32–35 40–42 44–46 48 51–53 59–81 and/or effectiveness of care, with a lack of focus on other domains of quality. The prioritisation on safety was not surprising given the well-recognised magnitude of the patient safety problem21 and the resultant global movement to improve patient safety.…”
Section: Discussionmentioning
confidence: 98%